Modelo de ashkin-teller de três cores na rede ponte de wheatstone - Oliveira, Roberto Teodoro Gurgel de (2010)
In this work we study the phase transitions of the ferromagnetic three-color Ashkin-Teller Model in the hierarquical lattice generated by the Wheatstone bridge using real space renormalization group approach. With such technique we obtain the phase diagram and its critical points with respective critical exponents v. This model presents four phases: ferromagnetic, paramagnetic and two intermediates. Nine critical points were found, three of which are of Ising model type, three are of four states Potts model type, one is of eight states Potts model type and the last two which do not correspond to any Potts model with integer number of states. iv